The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3109/0886022x.2014.930650
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of uncoupling protein-2 by genipin exacerbates diabetes-induced kidney proximal tubular cells apoptosis

Abstract: Renal tubular epithelial cell injury is a major pathological event that contributes to the development of diabetic kidney disease (DKD). Uncoupling protein-2 (UCP2), a mitochondrial membrane protein, has been reported to participate in the regulation of reactive oxygen species (ROS) generation, which contributes to tubular cell apoptosis induced by hyperglycemia. In this study, we found that genipin, a UCP2 inhibitor, dramatically boosted oxidative stress, attenuated antioxidative capacity, and exacerbated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…This indicates that mitochondrial uncoupling was occurring in the db/db mice. As we also observed an up-regulation of Ucp-2 gene expression, our data are consistent with this model and other studies demonstrating the protective nature of Ucp-2 from oxidative stress [76,77].…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that mitochondrial uncoupling was occurring in the db/db mice. As we also observed an up-regulation of Ucp-2 gene expression, our data are consistent with this model and other studies demonstrating the protective nature of Ucp-2 from oxidative stress [76,77].…”
Section: Discussionsupporting
confidence: 93%
“…Thereby, T2DM patients carrying the mutated UCP2 haplotype could have an increased risk for DKD development since UCP2 concentration in their kidneys might not be enough to compensate the oxidative stress produced by chronic hyperglycemia. In agreement with our hypothesis, a recent study showed that genipin, an UCP2 inhibitor, dramatically boosted oxidative stress in rat renal proximal tubular cells incubated with high glucose concentrations, and this exacerbated cellular apoptosis due to an increase in caspase-3 activation [ 48 ]. In addition, He et al .…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, UCP2 knockdown in NRK-52E tubular cells abolished the effect of TGF-b1 treatment, decreasing extracellular matrix production (Jiang et al, 2013). In contrast, Chen et al (2014) demonstrated that inhibition of UCP2 by genipin increased oxidative stress in rat proximal tubular cells treated with high glucose medium, and this led to increased cell apoptosis. UCP2 knockdown in renal mesangial cells of rats also increased oxidative stress, inflam-mation, and apoptosis in vitro (Di Castro et al, 2013).…”
Section: Discussionmentioning
confidence: 96%